The valuation of initial public offerings* - KRINSKY, I.; ROTENBERG, W. (Contemporary Accounting Research, 1989)
Abstract. This paper examines the empirical validity of hypothesized relationships between the initial value of unseasoned common shares and information revealed to outside investors. In addition to the direct accounting disclosures contained in the offering prospectus, the entrepreneur is believed to signal the firm's true value through the proportion of ownership retained in the firm and the selection of prestigious underwriting services. The underwriter, in turn, intermediates in the disclosure of information to investors and applies a fee schedule which provides outsiders with further indications of project quality. Résumé. Les auteurs examinent la validité empirique des relations dont ils posent l'hypothèse entre la valeur des actions ordinaires lors d'une émission initiale et l'information livrée aux investisseurs extérieurs. En plus de l'information comptable directe contenue dans le prospectus d'émission, l'entrepreneur s'attend à ce que le pourcentage de la participation qu'il conserve dans l'entreprise et la sélection de services de prise ferme prestigieux soient des indicateurs de la valeur véritable de l'entreprise. Le preneur ferme, à son tour, joue le rôle d'intermédiaire dans la communication d'information aux investisseurs et applique un barème de frais qui véhicule, aux yeux des investisseurs extérieurs, d'autres indications au sujet de la qualité de l'émission.